2017
DOI: 10.1002/cpp.2079
|View full text |Cite
|
Sign up to set email alerts
|

Pathways into psychopathology: Modeling the effects of trait emotional intelligence, mindfulness, and irrational beliefs in a clinical sample

Abstract: Self-perception constructs concerning one's beliefs about oneself have a major impact on the likelihood of developing psychopathological symptoms. Emotional perceptions captured by trait emotional intelligence were stronger predictors of psychopathology than either or both mindfulness and irrational beliefs in a clinical sample of adults. If the seed factors of psychopathology are mainly psychological, rather than mainly biological, and given that psychological constructs, like trait emotional intelligence, mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
54
1
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(71 citation statements)
references
References 101 publications
(125 reference statements)
8
54
1
8
Order By: Relevance
“…Further, lower scores in Trait EI seemed to predict worse mental health (higher scores in the SDQ). This result is consistent with extensive previous evidence, revealing that high Trait EI is a positive predictor of mental health [8,10,17,19,65]. On the other hand, catastrophizing had a positive relationship with the total score of SDQ, that is, the more the adolescents think in catastrophic ways, the more the difficulties during adolescence.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Further, lower scores in Trait EI seemed to predict worse mental health (higher scores in the SDQ). This result is consistent with extensive previous evidence, revealing that high Trait EI is a positive predictor of mental health [8,10,17,19,65]. On the other hand, catastrophizing had a positive relationship with the total score of SDQ, that is, the more the adolescents think in catastrophic ways, the more the difficulties during adolescence.…”
Section: Discussionsupporting
confidence: 91%
“…These authors indicated that Trait EI constituted a stronger predictor of psychopathology than mindfulness and that mindfulness was a stronger predictor than irrational thoughts. The study points out that Trait EI has direct effects on psychopathology and indirect effects through mindfulness and that Trait EI is a stronger predictor of psychopathology than mindfulness and irrational beliefs combined [10].…”
Section: Relationships Between Emotional Intelligence Mindfulness Amentioning
confidence: 91%
See 3 more Smart Citations